PENGARUH DIGITAL LEARNING DAN LITERASI KEUANGAN TERHADAP MOTIVASI KARIR MAHASISWA AKUNTANSI DENGAN SELF-EFFICACY SEBAGAI VARIABEL MODERATING - Putra, Kharisma Nugraha; Susanti, Wahyu Febri Eka; Yanida, Maria (PRIMA EKONOMIKA, 2026)
This study aims to analyze the influence of digital learning and financial literacy on accounting students’ career motivation, and to examine the moderating role of self-efficacy in these relationships. A quantitative survey approach was employed, involving accounting students who had experience using at least one digital learning application. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The hypothesis testing results show that digital learning has no significant effect on students’ career motivation, whereas financial literacy has a positive effect on career motivation. However, self-efficacy does not moderate the relationship between digital learning and career motivation, nor between financial literacy and career motivation. These findings indicate that the use of digital technologies in learning has not yet contributed meaningfully to students’ career orientation, while financial literacy appears to be more relevant in fostering students’ professional aspirations in the accounting field.